Impact of firm-specific characteristics on managers' identity disclosure. Issue 2 (19th August 2014) - Asien, Etumudon Ndidi
Abstract : Purpose: This paper examines the impact of firm-specific characteristics on managers' identity disclosure in the GCC region. Design/methodology/approach: Research data were collected from 2010 annual reports and financial statements of 403 listed firms in the GCC countries. The data were analyzed by multiple regression models. Findings: We document evidence suggesting that managers' identity is significantly disclosed by firms that separate the office of chairman from that of chief executive officer. We also find that mature firms significantly disclose their managers' identity. Our finding suggests that firms' declaration that they comply with a set of corporate governance code leads them to disclose managers' identity. However, we find that firms that are related to the state significantly disclose their managers' identity, contrary to expectation. Research limitations/implications: One limitation is the lack of a uniform classification of industries by the stock exchanges in the GCC region. The implication of this is that researchers are lacking a uniform standard to apply in their research. Another limitation is the use of only 2010 annual reports and accounts; so there is a problem of inter-temporal generalizability. As markets in the GCC countries are evolving, it will be interesting to capture the state of managers' identity disclosure after 2010. Practical implications: The paper has the potential to influence firms in the GCC region to begin disclosing managers' personal details and other contact information. Also, there is the prospect that market regulators in the GCC region and other emerging markets who may read this research may now require firms to disclose their managers' identity. Originality/value: This is an Original Research Paper